Clemastine protects against sepsis-induced myocardial injury in vivo and in vitro. Issue 3 (1st March 2022) - Wang, Xiaowan; Xie, Di; Dai, Hui; Ye, Jiawei; Liu, Yuqi; Fei, Aihua
ABSTRACT: Sepsis-induced myocardial dysfunction (SIMD) is associated with high morbidity and mortality rates; however, it lacks targeted therapies. Modulating cardiomyocyte autophagy maintains intracellular homeostasis during SIMD. Clemastine, a histamine receptor inhibitor, promotes autophagy and other effective biological functions. Nevertheless, the effect of clemastine on SIMD remains unclear. This study aimed to explore the underlying mechanism of clemastine in cardiomyocyte injury in cecum ligation and perforation (CLP)-induced rats and lipopolysaccharide (LPS)-stimulated H9c2 cells. Clemastine (10 mg/kg, 30 mg/kg, and 50 mg/kg) was intraperitoneally injected after 30 min of CLP surgery. Serum cTnI levels and the 7-day survival rate were evaluated. Echocardiograms and H&E staining were used to evaluate cardiac function and structure. TEM was used to detect the mitochondrial ultrastructure and autophagosomes. Clemastine significantly improved the survival rate and reduced cTnI production in serum. Clemastine ameliorated cellular apoptosis, improved mitochondrial ultrastructure both in vivo and in vitro, increased ATP content, decreased dynamin-related protein 1 (DRP1) expression, and decreased mitochondrial ROS levels. Additionally, clemastine treatment increased autophagosome concentration, LC3II/LC3I rate, and Beclin 1 expression. However, 3-methyladenine (3-MA), an autophagy inhibitor, could abolish the effect of clemastine on alleviating myocardial apoptosis. In conclusion, clemastine protected against cardiac structure destruction and function dysfunction, mitochondrial damage, apoptosis, and autophagy in vivo and in vitro . Moreover, clemastine attenuated myocardial apoptosis by promoting autophagy. This study provides a novel favorable perspective for SIMD therapy. Graphical Abstract: uf0001